Expression of transcription factors during oligodendroglial development - Wegner, Michael (Microscopy Research and Technique, 2001)
Transcription factors coordinate the orderly changes of gene expression that underlie all developmental processes including those of oligodendrocytes. In comparison to other systems, relatively little is known about the role of transcription factors during oligodendrocyte development. However, recent years have seen the identification of oligodendroglial transcription factors that, not surprisingly, belong to the same gene families that are also important in other tissues or cell lineages. Some transcription factors such as the bHLH (basic helix-loop-helix) proteins Olig-1 and Olig-2 or the high-mobility-group protein Sox10 are expressed already early during development of the oligodendrocyte lineage, whereas expression of other transcription factors such as the homeodomain protein Gtx/Nkx6.2 only start at the time of terminal differentiation. Once turned on, expression of these proteins can either be permanent as in the above-mentioned cases or transient as exemplified by the POU domain proteins Tst-1/Oct6/SCIP, Brn-1 and Brn-2. Analyses of these transcription factors has already led to the identification of important principles such as functional redundancy between co-expressed proteins, unexpected divergence in the transcription factor repertoire of oligodendrocytes and Schwann cells, and equally unsuspected similarities in transcription factor usage between oligodendrocytes and neurons. Although so far only a small percentage of oligodendroglial transcription factors has been identified, these are excellent candidates for regulators of cell type specification, lineage progression, and terminal differentiation. © 2001 Wiley-Liss, Inc.
UnivIS-Import:2015-03-09:Pub.2001.med.IB.LPCIPDBI.expres
Keywords: Gtx; Olig-1; Olig-2; Oligodendrocyte; Pax; Pelizaeus-Merzbacher disease; POU; Schwann cell; SCIP; Sox